ANALISIS PELAKSANAAN AKAD PADA PT. ASURANSI JIWA SYARIAH AL-AMIN CABANG PONTIANAK MENURUT FATWA-FATWA DSN-MUI TENTANG ASURANSI SYARIAH - Safira Kaddihan; Rusdi Sulaiman; Moch. Riza Fahmi (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
The purpose of this research is to find out the implementation of the Sharia insurance contract of PT Sharia Life Insurance Al-Amin Pontianak Branch and explain the implementation of the Fatwa-Fatwa of the National Sharia Council of the Indonesian Ulema Council on Sharia Insurance in the Implementation of the Agreement at PT Sharia Life Insurance Al-Amin Pontianak Branch. This research uses qualitative research methods with descriptive normative legal research. Primary data sources and secondary data. Data collection techniques using observation, interviews and documentation. Data validity was checked using triangulation of sources and techniques. The findings of this research include: 1). The implementation of the contract at PT Asuransi Jiwa Syariah Al-Amin Pontianak Branch uses a hybrid contract (multi-contract), namely a tijarah contract and a tabarru' contract. The tijarah contract is in the form of a wakalah bil ujrah contract with a profit-sharing system and a tabarru' contract in the form of grants and qardh. 2). In general, the implementation of the contracts carried out at PT. Al-Amin Syariah Life Insurance, Pontianak branch, namely the wakalah bil ujrah, tabarru' and qardh contracts are in accordance with the fatwas of the National Sharia Council of the Indonesian Ulema Council concerning Agreements in Sharia Insurance.